Subclinical psychosis in adult migrants and ethnic minorities: systematic review and meta-analysis. Issue 6 (November 2018) - Tortelli, Andrea; Nakamura, Aurélie; Suprani, Federico; Schürhoff, Franck; Van der Waerden, Judith; Szöke, Andrei; Tarricone, Ilaria; Pignon, Baptiste
Abstract : Background: It is well established that migration and ethnic minority status are risk factors for psychotic disorders. Recent studies have aimed to determine if they are also associated with subclinical psychosis (psychotic-like experiences and schizotypal traits). Aims: We aimed to determine to what extent migrant and ethnic minority groups are associated with higher risk of subclinical psychosis. Method: We conducted a systematic review, using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses statement, and examined findings by ethnicity, migrant status, outcomes of subclinical psychosis and host country. A meta-analysis was carried out with robust variance estimation where possible, to handle statistically dependent effect size estimates. Results: We included 28 studies (19 studies on psychotic-like experiences and 9 studies on schizotypal traits) and found that ethnicity, but not migrant status, was associated with current and lifetime psychotic-like experiences. In the narrative analysis, we observed the effect of psychosocial risk factors on this association: Black ethnicity groups showed consistent increased prevalence of current and lifetime psychotic-like experiences compared with the reference population across countries. Conclusions: More generalisable and standardised cohort studies of psychotic-like experiences and schizotypal traits in relation to migration/ethnicity are necessary to examine the effects of exposures and outcomes in different contexts, and to understand the underlying mechanisms of the association between subclinical psychosis and migrant and ethnic minority status. Declaration of interest: None.